A Review of Literature on Breast Cancer: Molecular Insights, Clinical Approaches, and Future Perspectives - Ritu; Anshika Rosha (International Journal of Oncological Nursing and Practices, 2025)
Breast cancer is the leading cause of morbidity and mortality in women globally. Although both men and women can get the condition, women are more likely to get it, and its prevalence has been rising globally in recent years. The epidemiology, risk factors, pathophysiology, diagnosis, treatment options, and survival rates of breast cancer are all examined in this review of recent research. Breast cancer can show up as a lump in the breast, changes in the breast's size or form, skin dimpling, or nipple discharge, among other signs. Screening methods that can identify issues early and enhance prognosis include magnetic resonance imaging (MRI), mammography, and ultrasonography. Breast tumors can be precisely classified using histopathological investigation and molecular profiling, which informs therapy choices. The study examines the molecular subtypes of breast cancer, the genetic and environmental factors that influence risk, and developments in early detection, including the function of screening programs. With a focus on the value of personalized medicine, treatment approaches such as surgery, chemotherapy, radiation, targeted therapy, and immunotherapy are examined. There are still issues, especially with aggressive subtypes like triple-negative breast cancer, despite advancements in research and treatment. Immunotherapy and molecular profiling are two potential future research avenues that could enhance survival rates and results.
Keywords: Mammography; Ultrasonography; estrogen receptor; menstruation; triple-negative breast cancer